Flood Detector Monitoring System using Raspberry Pi - Ahmad Aqil Haikal; Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2024)
Flooding is a serious issue for cities, leading to infrastructure damage, loss of property and threats to human safety. The project focuses on developing an advanced flood detection system that uses sensor technology and smart grids to provide real-time data on water levels and rainfall. Recent floods have caused significant displacement and damage, highlighting the need for better early warning systems. The main goal of this project is to create a flood monitoring system using Raspberry Pi that can detect water levels and rainfall in real time and send notifications via Telegram. The system includes a water level sensor that triggers alerts via LED lights and uses WiFi to send notifications. The system is designed with sensors to detect rain, microcontrollers to process data, and communication tools to send alerts. Our results show that the system can effectively warn both authorities and residents through sound alarms and mobile notifications. This flood monitoring solution offers a reliable and efficient way to add early flood warning and response, LCD indicators and Telegram notifications to provide a comprehensive flood monitoring solution. Trial results show that the system effectively provides clear visual and audible warnings, helping to reduce the risks associated with rising water levels